Process Evaluation of Implementing a Pharmacist-Led Intervention to Improve Adherence to Antihypertensive Drugs Among Patients with Type 2 Diabetes in Indonesian Community Health Centers - Alfian, Sofa D.; van Boven, Job F. M.; Iskandarsyah, Aulia; Abdulah, Rizky; Hak, Eelko; Denig, Petra (Frontiers in Pharmacology, 2021)
Introduction: A pharmacist-led intervention in Community Health Centers (CHCs) in Indonesia targeted at patients with type 2 diabetes non-adherent to antihypertensive drugs resulted in a significant improvement in adherence to these drugs. The aim of this study was to evaluate the process of implementation this intervention intended to improve adherence to antihypertensive drugs from both the pharmacist and the patient perspective. Methods: Using the RE-AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance) framework, we conducted a focus group among pharmacists (N=5) and a survey among patients with complete follow-up (N=44) participating in the intervention group. Results: All pharmacists adopted the provided training and found support tools useful. The pharmacists implemented the intervention as intended (adequate intervention fidelity >69%). Factors relevant for implementation included having sufficient time and confidence, home visits for specific patients, multidisciplinary collaboration, and availability of a personal counseling room. To maintain the intervention, the need for practical guidance and support from health care authorities was mentioned. Most patients (96%) were satisfied with the information provided by the pharmacists and they believed the tailored counselling was helpful. Most patients (84%) reported that the duration of counselling was sufficient. The large majority of patients would like to receive the counselling regularly. Conclusion: Positive effects of the pharmacist-led intervention can be explained by adequate levels of reach, adoption and implementation in the participating CHCs. For successful implementation and maintenance in Indonesia or other low- and middle-income countries, sufficient training, resources, multidisciplinary collaboration, guidance and support from health care authorities are expected to be important.